Exploring the attitudes and views of pre-primary and primary school teachers for climate change education. (4th November 2022) - Andrea, Veronika; Petkou, Dafni
The teachers' built-in perceptions and views towards climate change play a critical role in the processes of developing pro-environmental attitudes for their students and also in the formation of their students' environmental consciousness in the future. The study aims to examine the pre-primary and primary school teachers' attitudes and views on climate change and subsequently how their perceptions affect them in implementing environmental education programs focused on climate change. Simple random sampling was applied, while the data collection took place with the use of a structured questionnaire and personal interviews. The findings show that, although teachers acknowledge climate change global impacts, there is a need to enhance their environmental literacy, and their pedagogical and scientific skills to be able to help students develop participatory skills in environmental decision making.